Polypropylene Nanocomposites Obtained by in Situ Polymerization Using Metallocene Catalyst: Influence of the Nanoparticles on the Final Polymer Morphology - Zapata-Ramirez, P (2012)
Polypropylene nanocomposites containing silica nanospheres based on the sol-gel methods were produced via in situ polymerization using a rac-Et(Ind) 2ZrCl 2/methylaluminoxane (MAO) system. Two different routes were used depending on the interaction between the silica nanoparticles with the catalytic system. In route 1 the nanoparticles were added together with the catalytic system (rac-Et(Ind) 2ZrCl 2)/(MAO) directly into the reactor, and in route 2 the metallocene rac-Et(Ind) 2ZrCl 2 was supported on silica nanospheres pretreated with (MAO). SEM images show that when the nanospheres were added by both routes, they were replicated in the final polymer particle morphology; this phenomenon was more pronounced for PP obtained by route 2. The polypropylene (PP) nanocomposites obtained by both routes had a slightly higher percent crystallinities and crystallinity temperatures than pure PP. Transmission electron microscopy (TEM) images show that the nanospheres were well dispersed into the polypropylene matrix, particularly in the nanocomposites obtained by the support system (route 2). Copyright 2012 Paula Zapata and Ral Quijada.